KETIDAKPASTIAN DISTRIBUSI KUALITAS BATUBARA MENGGUNAKAN METODE INTERPOLASI PADA SITE BANKO TENGAH BLOK A, KABUPATEN MUARA ENIM, SUMATERA SELATAN - Dian Agus Widiarso; Ulfatunnisa; Nurakhmi Qadaryati (JURNAL GEOMINERBA (JURNAL GEOLOGI, MINERAL DAN BATUBARA), 2022)
Block A of Banko Tengah is a concession exploration area. Along with the increasing demand for electrical energy & the condition of diverse coal qualit,y so a feasibility study is needed for optimizing exploration activity. The research location is Lawang Kidul District, Muara Enim Regency, South Sumatra. Uncertainty studies are related to distribution, seam continuity, and spatial variability pattern, accordingly needed seam reconstruction and coal quality assessment based on drilling data and result of geochemical test analysis. Interpolation methods are kriging, inverse distance to power, and natural neighbor. The quality analysis results show that mine brand of A1 is GAR 4.200 LS, A2 is GAR 4.400 LS, B1 is GAR 4.400 LS, B2 is GAR 4.200 LS, C1 is GAR 4.600 HS, and C2 is GAR 4.400 LS. The statistical assessment was carried out on B1 because of continuity seam, good mine brand, and the most data. The effectiveness of the interpolation method is natural neighbor because the borehole points are pretty close (there is dense data in East-West & rare data in Northeast – East) and the variability of the actual data is quite low.